Rise of a merchant prince - Feist, Raymond E. (Feist, Raymond E. Serpentwar saga, 2012)
"Surviving the wrath of the fearsome Sauur--a hideous race of invading serpents--noble Erik and cunning Roo have delivered a timely warning to the rulers of the Midkemian Empire, and are now free to pursue their separate destinies. Erik chooses the army--and the continuing war against Midkemia's dread enemies. Roo lusts for wealth and power--rising high and fast in theworld of trade. But with luxury comes carelessness and a vulnerability to the desires of the flesh. And a beautiful seductress with her ruthless machinations threatens to destroy everything Roo has built and become--summoning catastrophe into his future...and terror into his world."--Publisher description.